(untitled) (Asian Journal of Ethnobiology, 2020)
Abstract. Afrianto WF, Tamnge F, Hasanah LN. 2020. Review: A relation between ethnobotany and bioprospecting of edible flower Butterfly Pea (Clitoria ternatea) in Indonesia. Asian J Ethnobiol 3: 51-61. Clitoria ternatea L., known as “bunga telang” in Indonesia, is an important medicinal plant to Fabaceae, an ornamental perennial climber. It has widely distributed throughout Africa, Asia, Australia, North and South America, Pacific (Northwestern, South-Central, and Southwestern). This review aims to study the relation between ethnobotany and bioprospecting of C. ternatea. The literature study revealed that Indonesian communities use flowers as part of C. ternatea as an eye medicine, boils disease, an ornamental plant, and a symbol in traditional ceremonies. Leaf, flower, seed, and root of this species have bioprospecting for medicine, agriculture, and food and beverage. Ethnobiology exploration of C. ternatea in Indonesia is an initial step to observe the bioprospecting potential. Then, further research can continue to produce commercial products that will provide an economic impact and motivate communities to take part in conservation actions. The present study assesses the minor works on bioecology, ethnobotany, bioprospecting, and market potential. We hope that the study‘s output can spur further research and industry approach.